Postpolymerization modification of a hydroxy monolith precursor. Part I. Epoxy alkane and octadecyl isocyanate modified poly (hydroxyethyl methacrylate‐co‐pentaerythritol triacrylate) monolithic capillary columns for reversed‐phase capillary electrochromatography. Issue 23 (4th October 2016) - Khadka, Shantipriya; El Rassi, Ziad
Abstract : A novel precursor monolithic capillary column referred to as "hydroxy monolith" or OHM was prepared by the in situ copolymerization of hydroxyethylmethacrylate (HEMA) with pentaerythritol triacrylate (PETA) yielding the neutral poly(HEMA‐co‐PETA) monolith. The neutral precursor OHM capillary thus obtained was subjected to postpolymerization modifications of the hydroxyl functional groups present on its surface with 1, 2‐epoxyalkanes catalyzed by boron trifluoride (BF3 ) ultimately providing Epoxy OHM C‐m capillary column at varying alkyl chain lengths where m = 8, 12, 14, and 16 for RP‐CEC. Also, the same precursor OHM was grafted with octadecyl isocyanate yielding Isocyanato OHM C‐18 column to provide an insight into the effect of the nature of the linkage to the surface hydroxyl groups of the OHM precursor. While the epoxide reaction leaves on the surface of the OHM precursor hydroxy‐ether linkages, the isocyanato reaction leaves carbamate linkages on the same surface of the OHM precursor. This study revealed that changing the alkyl chain length resulted in changing the column phase ratio (ϕ) and also the solute distribution constant ( K ). While increasing the surface alkyl chain length increased steeply the solute hydrophobic selectivity, i.e. methylene group selectivity, the nature of the ligand linkage produced different retention for the same solutes and affected the selectivity of slightly polar solutes. The various monoliths proved very useful for RP‐CEC of different small solutes at varying polarity over a wide range of mobile phase composition.